$\mathbb{A}_{\text{inf}}$ IS INFINITE DIMENSIONAL. (11th November 2021) - Lang, Jaclyn; Ludwig, Judith
Abstract: Given a perfect valuation ring $R$ of characteristic $p$ that is complete with respect to a rank-1 nondiscrete valuation, we show that the ring $\mathbb{A}_{\inf }$ of Witt vectors of $R$ has infinite Krull dimension.